Host-parasite Relationship in Cistanche spp. Hoffmgg. et Link1 - ABOU-RAYA, M. A.; EL-SHARKAWY, M. A.; EL-TAIFE, A. (The Libyan Journal of Agriculture, 2023)
This report is concerned with the two root-holoparasite species. Cistanche violacea (Desf.) G. Beck and C. phelypaea (L.) Cout.. of the Orobanchaceae. The former species exists in wild state in saline soils and is associated with a wide range of host species, mostly members of the Chenopodiaceae. On the other hand, the latter species (C. phelypaea) was mainly found parasitizing Tamarix aphylla (L.) Karst. Application of concentrated host exudate, host root extract, or some growth regulators to pre-treated seeds of the two Cistanche spp. did not stimulate the germination of most seeds. In fact, very few seeds which are less than 1% germinated spontaneously. Moreover, these seeds did not respond to an appropriate concentration of gum tragacanth extract which was supposed to transform their germ tubes into haustoria. It seems that in these two species there is a very specific requirement for germination and the subsequent development of haustoria. Using a special technique in which a fabric bag. containing those parasite seeds, was inserted close to the host root system of Tamarix aphylla, it was found that the host-parasite haustorial contact was accomplished by the host root itself growing towards and penetrating the seed. In fact, a single filiform host root may penetrate and string several parasite seeds one after the other. Within the seed the host root swells, forms root hair-like structure and becomes associated with callus tissue developing from the parasite seed embryo. This process is in sharp contrast with the hitherto known mechanism of host parasite contact where an exudate from the host root stimulates the emergence of the parasite germ tube and its subsequent chemotropic growth to host roots. Moreover, these new observations support the idea that both host root and the developing parasitic embryonic callus are involved in forming the primary haustorial-like structure.